Challenges in edge angle measurement during alpine skiing using IMU sensors - Hummel, C.; Huber, A.; Waibel, K.; Menhorn, F.; Spitzenpfeil, P. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: "To turn, a skier manipulates the orientation and loading pattern of skis to generate a reaction force from the snow surface that allows redirection of trajectory and regulation of speed" (Reid et al., 2020). Therefore, measurement edging angles allow for information about ski snow interaction and turning technique (Snyder et al., 2021). In this study, an algorithm is presented that allows us to measure ski orientation in 3D space using IMUs.